Factors influencing the utilization of the tetanus toxoid immunization program among pregnant women at terjun public health center, Marelan district - Anggreini, Dina; Nurhayati, Nurhayati; Aidha, Zuhrina (Institute of Computer Science (IOCS), 2025)
Neonatal tetanus remains a significant cause of infant mortality, particularly in developing countries, despite being preventable through Tetanus Toxoid (TT) immunization during pregnancy. This study aimed to analyze the factors influencing the utilization of TT immunization among pregnant women at Terjun Public Health Center, Marelan District. Using a cross-sectional quantitative approach, data were collected from 46 third-trimester pregnant women through questionnaires. Bivariate and multivariate analyses were conducted using chi-square tests and logistic regression. The results showed that knowledge (p=0.002) and attitude (p=0.001) were significantly associated with TT immunization uptake, while age (p=0.536) and spousal support (p=0.603) were not. Multivariate analysis revealed that attitude was the dominant factor influencing immunization utilization (OR=4.7; p=0.045). Although knowledge had a higher odds ratio (OR=5.59), it did not reach statistical significance (p=0.056). The model explained 38.9% of the variation in immunization status (Nagelkerke R² = 0.389). These findings underscore the importance of promoting positive maternal attitudes and improving knowledge through targeted health education to enhance immunization coverage and prevent neonatal tetanus